Academic visit by Universitas Ubudiyah Indonesia / Syahida Fathiah Ahmad Kamal and Assoc. Prof. Dr. Mahmathi Karuppannan - Ahmad Kamal, Syahida Fathiah; Karuppannan, Mahmathi (Faculty of Pharmacy, 2023)
On 11 March 2023, the Faculty of Pharmacy hosted an academic visit by five lecturers and 34 students from Universitas Ubudiyah Indonesia. The visit started with a welcoming session by Dr. Mohd Shahezwan Abd Wahab, the Deputy Dean of Academic Affairs. In this session, the delegation led by Dr. Arlayda was introduced to the academic programs, research expertise and services offered at the Faculty of Pharmacy, UiTM. Following that, two students representing the student council (MPP) were invited to share about student's activities at the faculty and a brief presentation on safe use of medicines.